2019
DOI: 10.3390/jcm8122150
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Acute Myocardial Infarction Among New Users of Allopurinol According to Serum Urate Level: A Nested Case-Control Study

Abstract: Objectives: To test the hypothesis that allopurinol reduces the risk of acute myocardial infarction (AMI) in hyperuricemic patients and to assess whether the effect is dependent on dose, duration and serum uric acid (SUA) level attained after treatment. Methods: Nested case-control study over the period 2002-2015. From a cohort of patients aged 40-99 years old, we identified incident AMI cases and randomly selected five controls per case, matched for exact age, sex and index date. Adjusted odds ratios (AOR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The benefit was only observed at higher doses (300 mg or higher) and prolonged treatment duration (> 180 days) [ 63 ]. Similar observations have been reported by Rodriguez-Martin et al regardless the presence of gout [ 67 ]. Grimaldi-Bensouda et al also found a reduced risk in those who used allopurinol (adjusted OR 0.73 (95% CI 0.54 to 0.99) [ 64 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The benefit was only observed at higher doses (300 mg or higher) and prolonged treatment duration (> 180 days) [ 63 ]. Similar observations have been reported by Rodriguez-Martin et al regardless the presence of gout [ 67 ]. Grimaldi-Bensouda et al also found a reduced risk in those who used allopurinol (adjusted OR 0.73 (95% CI 0.54 to 0.99) [ 64 ].…”
Section: Resultssupporting
confidence: 91%
“…In the included trials, a total of 3080 patients have been allocated to either allopurinol (n = 1638) or no-urate-lowering therapy (n = 1442). In total 21 observational studies were included: 16 cohort studies (4 prospective [ 47 50 ] and 12 retrospective [ 51 62 ]), and 5 case-control studies [ 63 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cardioprotective effect against myocardial injury by uricosuric drugs such as probenecid or allopurinol was generally believed as a consequence of reduction in serum uric acid levels (Padda et al, 2021; Rodriguez‐Martin et al, 2019).…”
Section: New Targets and Perspectives Of Probenecidmentioning
confidence: 99%
“…When new drugs such as allopurinol were introduced to the market, uricosuric agents such as probenecid were recommended as second‐line options in the treatment of gout. As with other anti‐gout medications such as canakinumab, colchicine or allopurinol (Nidorf et al, 2020; Ridker et al, 2017; Rodriguez‐Martin et al, 2019), probenecid has been regaining some interest to be repositioned for cardiovascular indications. It has been shown to act on other targets including pannexins and TRPV2 cation channels or purinergic receptors, exerting anti‐inflammatory and cytoprotective effects (Jung et al, 2020; Koch et al, 2012; Rosli et al, 2019; W. Silverman et al, 2008; Wonnenberg et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Antigout drugs (M04) Myocardial infarction 56,57 Anti-osteoporotic drugs (M05B) Fractures 58,59 Venous thromboembolism 60 b Trends The steps needed to perform a study in BIFAP are summarized in Figure 3. In the process, registered investigators receive training and additional support on a case by case basis before the delivery of the analytical dataset.…”
Section: Indication 55mentioning
confidence: 99%